Investigating the effect of DG infeed on the effective cover of distance protection scheme in mixed-MV distribution network - Saad Muftah Saad; Naser El Naily; Faisal A. Mohamed (International Journal of Renewable Energy Development, 2018)
The environmental and economic features of renewable energy sources have made it possible to be integrated as Distributed Generation (DG) units in distribution networks and to be widely utilized in modern distribution systems. The intermittent nature of renewable energy sources, altering operational conditions, and the complex topology of active distribution networks makes the level of fault currents significantly variable. Thus, the use of distance protection scheme instead of conventional overcurrent schemes offers an appropriate alternative for protection of modern distribution networks. In this study, the effect of integrating multiple DG units on the effective cover of distance protection schemes and the coordination between various relays in the network was studied and investigated in radiology and meshed operational topologies. Also, in cases of islanded and grid-connected modes. An adaptive distance scheme has been proposed for adequate planning of protection schemes to protect complex networks with multiple distribution sources. The simplified simulated network implemented in NEPLAN represents a benchmark IEC microgrid. The comprehensive results show an effective protection measure for secured microgrid operation.Article History: Received October 18th 2017; Received in revised form May 17th 2018; Accepted July 8th 2018; Available onlineHow to Cite This Article: Saad, S.M., Naily, N.E. and Mohamed, F.A. (2018). Investigating the Effect of DG Infeed on the Effective Cover of Distance Protection Scheme in Mixed-MV Distribution Network. International Journal of Renewable Energy Development, 7(3), 223-231.https://doi.org/10.14710/ijred.7.3.223-231